2008
DOI: 10.1002/cncr.23242
|View full text |Cite
|
Sign up to set email alerts
|

Manipulative therapy of secondary lymphedema in the presence of locoregional tumors

Abstract: BACKGROUND. Complete decongestive therapy (CDT), including manual lymphatic drainage (MLD) is a manipulative intervention of documented benefit to patients with lymphedema (LE). Although the role of CDT for LE is well described, to the authors' knowledge there are no data regarding its efficacy for patients with LE due to tumor masses in the draining anatomic bed. Traditionally, LE therapists are wary of providing therapy to such patients with ‘malignant’ LE for fear of exacerbating the underlying cancer, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0
3

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(27 citation statements)
references
References 7 publications
1
21
0
3
Order By: Relevance
“…Of the 36 English-language studies, 30 were RCTs [11,21-41,43-50] and six were observational (cohort) [51-56]. Fifteen RCTs were fair quality [21,22,25,26,29-32,36,43-47,50], eight were good quality [11,24,27,35,38,41,48,49], and seven were poor quality [23,28,33,34,37,39,40].…”
Section: Resultsmentioning
confidence: 99%
“…Of the 36 English-language studies, 30 were RCTs [11,21-41,43-50] and six were observational (cohort) [51-56]. Fifteen RCTs were fair quality [21,22,25,26,29-32,36,43-47,50], eight were good quality [11,24,27,35,38,41,48,49], and seven were poor quality [23,28,33,34,37,39,40].…”
Section: Resultsmentioning
confidence: 99%
“…There is also controversy over the role and safety of manual therapies and acupuncture in the management of lymphedema postcancer treatment (64,65). Although some studies have concluded that such treatment is safe even in areas with residual tumor (66)(67)(68), to date, no randomized prospective study has examined this issue. Meanwhile, there is virtually no basic research on physical manipulation of the connective tissue matrix surrounding tumors to influence the behavior of the tumor as it interacts with its surrounding matrix, or at distant sites to influence the receptivity of the matrix to metastatic seeding.…”
Section: Potential Effects Of Physical-based Treatments On Cancermentioning
confidence: 99%
“…Ha az onkológiai kezelés palliatív célból történik, palliatív ödé-mamentesítésről beszélünk, amely szükség esetén kiegé-szítendő palliatív sebkezeléssel és fájdalomcsillapítással. Számos szerző érvel amellett, hogy a manuális drenálás végzése nem kontraindikált áttétes tumor fennállása esetén, de ilyen esetben a manuális drenálást az adott helyzethez kell adaptálni [15][16][17][18][19]. Elméletileg ugyan a nyirokkollektorokban már jelen lévő tumorthrombusokat befolyásolhatja a manuális drenálás vagy a kompresszió, de a nemzetközi konszenzus is elismerte a KÖK alkalmazásának palliatív előnyeit aktív tumor fennállásakor [11].…”
Section: Terápiaunclassified
“…Ilyen módosítások lehetnek: a tumor vagy áttét által érintett bőrterületek elkerülése a manuális drenálás során; a standard kezeléshez képest alacsonyabb nyomással felhelyezett fásli; a kifekélyesedő tumor sebellátása; plegiás vég-tagra adaptált gyógytorna stb. Pinell és mtsai által végzett klinikai vizsgálat szerint a KÖK lokoregionális tumor fennállása esetén is ugyanolyan hatékonynak bizonyult, bár hosszabb kezelési időre volt ehhez szükség, mint tumormentes szekunder nyiroködémás betegekben [18].…”
Section: Terápiaunclassified